دراسة تحليلية لمسرحيات د. صلاح عدس الشعرية "البعث" أنموذجا: An Analytical Study of Dr Salah Adas Poetic Plays “Alba’s” as Model - Usman Farooq; Dr. Shakeel Ahmad (Al Manhal Research Journal, 2024)
Poetic play is one of the most important literary arts, mixing lyrical poetry with play. This type of play is based on poetic specifications, whether vertical or free poetry. It includes a set of elements that we can call the characteristics of the poetic play like language, style, plot, conflict, imagery , characters, dialogue, symbols etc. So we dealt in this analytical study with the poetic play and its characteristics through the play “Al-Ba’s” written by the renowned Egyptian poet, critic and playwright Dr. Salah Adas. This genre of poetry is an important part of Arabic literature and it is a new contribution to Arabic poetry. The first attempt of poetic play in Arabic literature was made by Khalil Al- Yaziji, meanwhile the most famous poet in this field is the Egyptian poet, Ahmed Shauqi, who made a great effort to develop dramatic poetry. It was unknown until Shauqi came and showed it to Arab people. Hence, this kind of poetry achieved much popularity among Arabs and Shawqi has been regarded as the father of dramatic poetry as well. Apart from that, the writers and critics also assumed him as the pioneer of this kind of poetry because of his great contribution. These attempts continued after Shawqi, in which there were large numbers of contemporary Arab poets who came to this field and imitated the styles and methods of Shawqi in writing dramatic poetry. Among the most famous people were Aziz Abaza, Ali Ahmed Bakthir , Salah Abdul Saboor and Abdul Rehman Sharqawi . Then, this kind of poetry develops completely until it reached an advanced stage of artistic maturity; therefore, it managed to have an excellent position in modern Arabic literature. The play “Al-Ba’s” is Islamic in its theme although its subject is Christian. It deals with the period of Roman emperor Decius’ persecution and brutality in Egypt. The dramatic conflict in it takes place between the martyred Dimyana (heroine in the play) and the tyrant Decius, who tortured her so that she would return to paganism, but she refuses and resists until death. The play “Al-Ba’s” has a precise artistic plot: the idea of steadfastness against religious persecution and oppression because it is the path to victory and freedom. Dr. Salah Adas distinguished his play “Al-Ba’s” with special features; Victory for truth and good, and defeat for falsehood and evil. We find in the play a horizontal conflict between truth and falsehood. It is interested in presenting positive personalities who fight for higher moral values. This article deals with the poetic play “Al-Ba’s” as a model of playwright's craftsmanship and mastery.